Robert Lepage/Ex Machina : revolutions in theatrical space - Reynolds, James (Senior lecturer in drama) (Methuen Drama engage, 2019)
"Robert Lepage/Ex Machina: Revolutions in Theatrical Space provides an ideal introduction to one of our most innovative companies - and a much-needed and timely reappraisal of Lepage's oeuvre. International, interdisciplinary and intercultural to the core, Ex Machina have negotiated some of the most complex creative and cultural challenges of our time. This book maps the story of that journey by analysing the full spectrum of their richly varied work. Through a comprehensive historiography of productions since 1994, Robert Lepage/Ex Machina offers a detailed picture of the relationship between director and company, while connecting Ex Machina to culturally specific features of QueÌbec, and its theatre. This book reveals for the first time how overlooked aspects of creativity and culture shaped the company's early work, while installing a dynamic interplay between director and company that would spark a unique and ongoing evolution of praxis. Central to this re-evaluation of practice is the book's identification of an architectural aesthetic at the heart of Ex Machina's work, an aesthetic which provides its artistic and political centres of gravity. Moreover, this architectural aesthetic powers the emergence of concrete narrative as a new and distinctive mode of theatrical storytelling - uniting story and space, body and technology, content and form - and demanding that we discover the politics of these performances in the energetic gestures of theatre design, and space itself. Drawing on extensive interviews with Lepage, Ex Machina personnel and collaborative partners, Robert Lepage/Ex Machina calls upon us to revise both our creative and critical perceptions of this vital and distinctive practice"--